Titanium Dioxide Visible Light Photocatalysis: Surface Association Enables Photocatalysis with Visible Light Irradiation - Pitre, Spencer P. (Chem Commun (Camb), 2017)
Titanium dioxide (TiO(2)) is a widely employed and inexpensive photocatalyst, but its use in organic synthesis has been limited by the short-wavelength ultraviolet irradiation typically used. We have discovered that TiO(2) particles efficiently mediate photocatalytic radical cation Diels-Alder cycloadditions using a simple visible light source, enabled by the formation of a visible light absorbing complex of the substrate on the semiconductor surface.